Diagnostic performance of next-generation sequencing and genetic profiling in thyroid nodules from a single center in China. Issue 3 (27th May 2022) - Ren, Min; Yao, Qianlan; Bao, Longlong; Wang, Zhiting; Wei, Ran; Bai, Qianming; Ping, Bo; Chang, Cai; Wang, Yu; Zhou, Xiaoyan; Zhu, Xiaoli
Abstract : Objective: The data regarding the mutation landscape in Chinese patients with thyroid cancer are limited. The diagnostic performance of thyroid nodules by fine-needle aspiration (FNA) cytology needs optimization, especially in indeterminate nodules. Methods: A total of 1039 FNA and surgical resection samples tested using the targeted multigene next-generation sequencing (NGS) panel were retrospectively collected. The features of gene alterations in different thyroid tumors were analyzed, and the diagnostic efficacy was evaluated. Results: Among 1039 samples, there were 822 FNA and 217 surgical FFPE samples. Among 207 malignant thyroid resections, a total of 181 out of 193 papillary thyroid carcinomas (PTCs) were NGS-positive (93.8%), with a high prevalence of BRAF mutations (81.9%, 158/193) and a low prevalence of RAS (1.0%, 2/193) and TERT promoter mutations (3.6%, 7/193). Gene fusions, involving the RET and NTRK3 genes, were present in 20 PTCs (10.4%) and mutually exclusive with other driver mutations. Two of three follicular thyroid carcinomas harbored multiple mutations. RET gene point mutations were common in medullary thyroid carcinoma (8/11, 72.7%). The combination of cytology and DNA–RNA-based NGS analysis demonstrated superior diagnostic value (98.0%) in FNA samples. For indeterminate thyroid nodules, the diagnostic sensitivity and specificity of NGS testing were 79.2 (38/48) and 80.0% (8/10), respectively. Two mutation-positive benign cases harbored NRAS and TSHR mutations, respectively. Conclusions: Our study revealed the distinct molecular profile of thyroid tumors in the Chinese population. The combination of NGS testing and FNA cytology could facilitate the accurate diagnosis of thyroid nodules, especially for indeterminate nodules.